Precarizations of Female Labor and Recognition. Narrative Traces of Female Workers in the Chilean Retail Industry (Palimpsesto, 2022)
The objective of the article is to present an analysis of the subjective dimensions of the processes of labor precariousness of women workers in the retail industry in Santiago de Chile, understood from the recognition theory. Methodologically, the article presents the reconstruction and in-depth analysis of three narratives of women workers in this industry, addressing the consequences of the processes of job insecurity, work processes and social protection conditions. The text concludes by showing how the cases bear witness both to forms of subjectivation from precariousness, and to how this produces moral grievances understood as alienation and dispossession from/at work.
Keywords: Female workers; Recognition; Retail; Narratives